P22 Early experience of multi-sequence fetal cardiac magnetic resonance imaging within a clinical fetal cardiology service. (2nd March 2016) - Lloyd, David F A; van Amerom, Joshua P; Pushparajah, Kuberan; Simpson, John; Zidere, Vita; Miller, Owen; Sharland, Gurleen; Allsop, Joanna; Fox, Matthew; Malamateniou, Christina; Hajnal, Jo; Rutherford, Mary; et al.
Abstract : Background: Fetal cardiac MRI offers the potential for a safe, radiation-free adjunct to echocardiography. In practice, its use has been limited by the technical challenges imposed by the small size of the fetal heart, the lack of external gating, and gross fetal and maternal movements. We present our initial experience of 20 fetal cases assessed by MRI, referred after routine fetal cardiology assessment to resolve specific points of diagnostic uncertainty. Methods: Referrals were based on the judgements of the attending fetal cardiologists between June 2014 and May 2015. Following a three-plane localiser, gross fetal movement was assessed with a balanced steady-state free precession (bSSFP) cine. Half-Fourier single-shot turbo spin echo (HASTE) and bSSFP gradient echo sequences were used for diagnostic imaging. The MRI diagnosis was subsequently compared with postnatal findings. Results: 20 fetal cardiac MRI scans were performed over the referral period, at an average gestational age of 32 +4 weeks, (range 26 +4 –38 +1 weeks). 3 scans were abandoned due to excessive fetal movement or inadequate visualisation. The most frequent referral indications were suspected coarctation of the aorta/abnormal arch anatomy (n = 9), cardiac masses or diverticulums (n = 5), and assessment of pulmonary vasculature (n = 4). HASTE sequences produced T2-weighted "black-blood" images, useful for assessing extracardiac vasculature (figure 1 ). Balanced SSFP sequences showed good contrast between the blood pool and surrounding tissue and were useful for intracardiac structures; however these were more susceptible to motion artefacts. Real-time SSFP sequences allowed for dynamic assessment of moving structures (e.g. masses/diverticulums-figure 2 ). Using a combination of sequences we were able to accurately characterise rhabdomyomas in 3 patients. In total, of the 17 scans with useful data, MRI was diagnostic in 15. Neonatal coarctation was incorrectly predicted in one case, and no postnatal data was available in another due to fetal demise. Conclusions: Certain fetal cardiovascular abnormalities may be difficult to diagnose with ultrasound alone, reflected in the referral pattern we observed for MRI. Our preliminary experience suggests that MRI can provide safe and useful complimentary imaging in this cohort within a tertiary fetal cardiac unit. As technical challenges continue to be addressed, prenatal MRI may develop a more prominent role in routine fetal cardiovascular assessment.